问题 解答题
把下列式子因式分解:
(1)a2b+2ab+b;
(2)-a3+a2b-
1
4
ab2
(3)(x+y)2-4(x+y-1);
(4)(x2+y22-4x2y2
(5)(x2-2x)2+2(x2-2x)+1;.
(6)(x+y)2-6x2+6y2+9(x-y)2
答案

(1)a2b+2ab+b

=b(a2+2a+1)

=b(a+1)2

(2)-a3+a2b-

1
4
ab2

=-a(a2-ab+

1
4
b2

=-a(a-

1
2
b)2

(3)(x+y)2-4(x+y-1)

=(x+y)2-4(x+y)+4

=(x+y-2)2

(4)(x2+y22-4x2y2

=(x2+y2+2xy)(x2+y2-2x)

=(x+y)2(x-y)2

(5)(x2-2x)2+2(x2-2x)+1

=(x2-2x+1)2

=(x-1)4

(6)(x+y)2-6x2+6y2+9(x-y)2

=(x+y)2-6(x2-y2)+9(x-y)2

=(x+y)2-6(x+y)(x-y)+9(x-y)2

=(x+y-3x+3y)2

=(-2x+4y)2

=4(x-2y)2

单项选择题
单项选择题